2018
DOI: 10.5606/tgkdc.dergisi.2018.14985
|View full text |Cite
|
Sign up to set email alerts
|

Early and late results in surgical excision of primary cardiac tumors: Our single-institution experience

Abstract: Bu çalışmada kalp kitlelerinin cerrahi eksizyonuna ilişkin deneyimimiz sunuldu ve bu hastaların sağkalım özellikleri incelendi. Ça lış ma pla nı: Ocak 2004-Aralık 2015 tarihleri arasında merkezimizde primer kardiyak tümör ile ameliyat edilen toplam 131 hasta (88 kadın, 43 erkek; ort. yaş 49.4±16.2 yıl; dağılım 1.2 ay-81 yıl) bu çalışmaya alındı. Demografik ve hastalara ilişkin diğer veriler, merkezimizin tıbbi kayıtlarından retrospektif olarak incelendi. Bul gu lar: Tüm benign tümörler tamamen rezeke edilirken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…After surgical resection, the main difference between benign and malignant tumors is the survival rates 6,17,18 . In our series, surgical resection of PCT has good short and long‐term results; conversely, the prognosis of malignant types is poor.…”
Section: Discussionmentioning
confidence: 58%
“…After surgical resection, the main difference between benign and malignant tumors is the survival rates 6,17,18 . In our series, surgical resection of PCT has good short and long‐term results; conversely, the prognosis of malignant types is poor.…”
Section: Discussionmentioning
confidence: 58%
“…Prior to catheter-based techniques, the conventional approach to intracardiac masses and cavo/atrial thrombus has been either conservative medical therapy with anticoagulation or surgical excision in the case of malignancy with possible adjuvant chemotherapy and/or radiation [3] . The overall in-hospital mortality associated with surgical excision of right heart masses may be up to 40 % depending on etiology and presentation [4] , [5] . By comparison, a meta-analysis of 42 studies including 182 patients undergoing percutaneous aspiration of right heart masses showed an overall mortality rate of 14.8 % [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is the treatment of choice for myxomas with low morbidity and mortality. Long-term mortality (>30 days) was 11.5%, with no in-hospital mortality in a study done on 131 patients, and the mean survival was reported to be 130.6 ± 4.5 months [ 9 ]. Our patient underwent a successful surgical resection along with valve repair.…”
Section: Discussionmentioning
confidence: 99%